2005
DOI: 10.1002/ajpa.20244
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Evidence for Breastfeeding and Possible Adult Dietary Differences from Late/Sub-Roman Britain

Abstract: Historical documents indicate that breastfeeding and weaning practices have fluctuated in England through history. In order to obtain evidence for general breastfeeding patterns in Late/Sub-Roman Britain, stable carbon and nitrogen isotope values were measured in juvenile and adult skeletons (n = 87) from the cemetery of Queenford Farm, Dorchester-on-Thames, Oxfordshire. As the site contained few individuals between 0-1.5 years of age, it was not possible to determine the initial timing for the introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
144
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 60 publications
13
144
1
7
Order By: Relevance
“…They reported that supplementary foods (boiled honey or a mixture of honey and goat's milk) were introduced gradually at 6 months of age, with complete termination of breastfeeding by 3 years of age. During the weaning process, the introduction of supplementary foods results in a gradual depletion of infant δ 15 N, reaching adult values when the child is fully weaned (Dupras et al, 2001;Fuller et al, 2006). Average enrichment in bone δ 13 C co and δ 15 N values of the humans analysed (at approximately 1.5‰ and 3.8‰, respectively), is consistent with a trophic level enrichment between herbivores and carnivores.…”
Section: Dietary Patternsmentioning
confidence: 53%
See 3 more Smart Citations
“…They reported that supplementary foods (boiled honey or a mixture of honey and goat's milk) were introduced gradually at 6 months of age, with complete termination of breastfeeding by 3 years of age. During the weaning process, the introduction of supplementary foods results in a gradual depletion of infant δ 15 N, reaching adult values when the child is fully weaned (Dupras et al, 2001;Fuller et al, 2006). Average enrichment in bone δ 13 C co and δ 15 N values of the humans analysed (at approximately 1.5‰ and 3.8‰, respectively), is consistent with a trophic level enrichment between herbivores and carnivores.…”
Section: Dietary Patternsmentioning
confidence: 53%
“…The δ 15 N collagen ratios of four other infants analysed (HMC 3, 4, 16 and 17; aged 38 weeks in uterus-1.5 months, 6 months-1 year, three and five years old) plot closely to the adult isotope ratios, suggesting that these individuals were either not breastfed or had already been weaned (Budd et al, 2013). Weaning practices of the Roman era were described by Soranus and Galen, medical scholars of the Roman world (2 nd century AD) (Dupras et al, 2001;Fuller et al, 2006). They reported that supplementary foods (boiled honey or a mixture of honey and goat's milk) were introduced gradually at 6 months of age, with complete termination of breastfeeding by 3 years of age.…”
Section: Dietary Patternsmentioning
confidence: 73%
See 2 more Smart Citations
“…While the plant diet of this individual was near the average value of all individuals presented here (32.3 ± 12.8 % C 3 , 32.8 ± 7.3 % C 4 ), the model indicates that they were consuming more terrestrial mammal meat (as compared to legumes) than any of the other analyzed individuals. In part, at least, the high modeled value for terrestrial mammal meat could be a consequence of an elevated δ 15 N co signature (15.0 ‰) resulting from the residual effects of breastfeeding (see, for example, Fuller et al 2006). It is worth noting, however, that this individual was also buried with an entire juvenile camelid and a hallucinogenic snuff tray with Tiwanaku iconography depicting a camelid carrying a bundle, possibly including plants (Fig.…”
Section: Discussionmentioning
confidence: 98%